Trauma in elderly patients: a study of prevalence, comorbidities and gender differences - GIOFFRÈ-FLORIO, M. (G Chir, 2018)
AIM: Trauma, in geriatric patients, increases with age, and is a leading cause of disability and institutionalization, resulting in morbidity and mortality. The aim of our study was to analyse the prevalence of trauma, the related risk factors, mortality and sex differences in the prevalence in a geriatric population. PATIENTS AND METHOD: We observed 4,554 patients (≥65 years) with home injuries or car accidents. Patients were evaluated with ISS (Injury Severity Score) and major trauma with ATLS (Advanced Trauma Life Support). The instrumental investigation was in the first instance, targeted X-Ray or whole-body CT. RESULTS: In over four years of study we treated 4,554 geriatric: 2,809 females and 1,745 Males. When the type of trauma was analysed the most common was head injury, followed by fractures of lower and upper limbs. In our experience hospitalization mainly involved patients over 80. In all patients mortality during assessment was 0.06%. DISCUSSION: The geriatric patient is often defined as a “frail elderly”, for the presence of a greater “injury sensitivity”. This is due to the simultaneous presence of comorbidity, progressive loss of full autonomy and exposure to a high risk of traumatic events. Optimal management of the trauma patient can considerable reduce mortality and morbidity. CONCLUSIONS: Falls and injuries in geriatric age are more frequent in women than in men. Among typical elder comorbidities, osteoporosis certainly causes a female preponderance in the prevalence of fractures. Our discharge data demonstrate that disability, which requires transfer to health care institutions, has a greater effect on women than men.